Frequency of Common Risk Factors of Pneumonia in Children Aged 2-59 Months: A Cross-Sectional Study - Shahzad Ahmed, Zamir Ahmed Qambrani, Nazimuddin, Shazia Mahar, Ainey Razzak, Muhammad Hayat, Muhammad Nadeem Chohan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim:-To determine the frequency of common risk factors of pneumonia in children aged 2-59 months visiting tertiary care hospital Study design: A cross-sectional study Place and Duration: National Institute of Child Health (NICH) Karachi from February to July 2018 Methodology: A total of 157children with complaints of fever 102F (or 39C), cough and tachypnea (≥50br/min from 2 to 11 months of age and ≥40br/min from 12 to 59 months of age) of less than two weeks duration were included in this study. Data was collected from both out-patient and indoor departments with patients fulfilling inclusion criteria after taking informed consent from their mother and risk factors were evaluated as mentioned in proforma. Results: Inappropriate immunization, Lack of breastfeeding, Malnutrition and upper respiratory tract infection in the mother were the commonest risk factors associated with pneumonia comprising 77.7%, 73.9%, 64.3% and 15.3% respectively. Conclusion: Our data suggest that non-breastfeeding or lack of breastfeeding during the neonatal period, inappropriate immunization, malnutrition, and upper respiratory tract infection in the mother may substantially increase the incidence and duration of pneumonia in children. Keywords: Pneumonia, Immunization, Respiratory tract infection, Lack of breastfeeding, Malnutrition